2008
DOI: 10.2147/vhrm.s2445
|View full text |Cite
|
Sign up to set email alerts
|

Early seizures in patients with acute stroke: Frequency, predictive factors, and effect on clinical outcome

Abstract: Background: Early seizure (ES) may complicate the clinical course of patients with acute stroke. The aim of this study was to assess the rate of and the predictive factors for ES as well the effects of ES on the clinical outcome at hospital discharge in patients with fi rst-ever stroke. Patients and methods: A total of 638 consecutive patients with fi rst-ever stroke (543 ischemic, 95 hemorrhagic), admitted to our Stroke Unit, were included in this prospective study. ES were defi ned as seizures occurring with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 32 publications
3
12
2
Order By: Relevance
“…In particular, a recent study conducted with the same prospective design and similar patient selection criteria, reporting data from stroke units and neurologic departments in Italy, found a 6.3% rate of ES, a figure slightly higher than our estimates [20]. Since stroke complications were not recorded in that analysis, as in others [21,22,23,24,25,26,27,28,29], however, we cannot rule out the possibility that such discrepancies might depend on different rates of complications among the studies.…”
Section: Discussioncontrasting
confidence: 48%
“…In particular, a recent study conducted with the same prospective design and similar patient selection criteria, reporting data from stroke units and neurologic departments in Italy, found a 6.3% rate of ES, a figure slightly higher than our estimates [20]. Since stroke complications were not recorded in that analysis, as in others [21,22,23,24,25,26,27,28,29], however, we cannot rule out the possibility that such discrepancies might depend on different rates of complications among the studies.…”
Section: Discussioncontrasting
confidence: 48%
“…However, our results with the PT model demonstrated that early poststroke seizures were restricted primarily to large cortical lesions, whereas smaller photothrombotic lesions did not induce seizures. This observation supports previous clinical data in which the probability of early seizures was higher in patients with stroke with larger lesions 44,45 . The photothrombosis model differs in the extent and nature of vessel occlusion; however, more importantly, unlike other stroke models, it shows almost no ischemic penumbra due to intense necrotization.…”
Section: Discussionsupporting
confidence: 89%
“…The present study investigated the incidence and temporal profiles of seizures as well as imaging characteristics in patients with PSE using modern VLSM. The incidence of PSE within 90 days of stroke onset in our prospectively collected cohort with first‐ever ischemic stroke was 2.8%, which is lower than reported in previous work 1,3,5,14,15 . This discrepancy may be attributed to the fact that previous investigators evaluated PSE in patients with hemorrhagic as well as ischemic strokes with variable times of follow‐up 1,3,5,14 .…”
Section: Discussioncontrasting
confidence: 74%
“…1,3,5,14,15 This discrepancy may be attributed to the fact that previous investigators evaluated PSE in patients with hemorrhagic as well as ischemic strokes with vari-able times of follow-up. 1,3,5,14 Hemorrhagic stroke has a higher risk for PSE than ischemic stroke. All patients in our cohort had a follow-up of 90 days after stroke onset.…”
Section: Discussionmentioning
confidence: 99%